2015
DOI: 10.1136/bcr-2014-209092
|View full text |Cite
|
Sign up to set email alerts
|

Large mitral valve aneurysm with infective endocarditis

Abstract: SUMMARYA 63-year-old man with infective endocarditis (IE) was admitted to our hospital after experiencing acute heart failure. A two-dimensional transthoracic and transesophageal echocardiography revealed vegetation attached to both aortic and mitral valves, a very large mitral valve aneurysm, a severe mitral regurgitation jet issuing from a mitral valve perforation and severe aortic regurgitation. Three days after admission, both the aortic and mitral valves were replaced. The patient received antibiotic ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…These cases suggest that MVA formation can be attributed to various factors, such as elderly calcified vascular disease, mitral valve prolapse, or other isolated vulvitis. All the MVAs in our study were detected on the anterior mitral leaflet, consistent with most previous reports (2,4,9,10,12,13,22,25,29,30). However, some case studies have reported MVAs on the posterior mitral leaflet (31)(32)(33)(34)(35)(36)(37), possibly induced by inflammation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These cases suggest that MVA formation can be attributed to various factors, such as elderly calcified vascular disease, mitral valve prolapse, or other isolated vulvitis. All the MVAs in our study were detected on the anterior mitral leaflet, consistent with most previous reports (2,4,9,10,12,13,22,25,29,30). However, some case studies have reported MVAs on the posterior mitral leaflet (31)(32)(33)(34)(35)(36)(37), possibly induced by inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…The reported MVA formation mechanisms include direct extension of infection from the aortic valve to the anterior mitral leaflet, impingement of aortic valve regurgitation on the anterior mitral valve leaflet, contact of aortic valve vegetation with the anterior mitral leaflet (kissing lesions), and mitral valve infections (3,5,8,9,12,(21)(22)(23)(24)(25)(26)(27). Aortic valve endocarditis (AVE) is considered the most common cause of MVA (3,4,6,7,9,24,25,28). In our study, 15 out of 20 patients were clinically diagnosed with infective endocarditis, and among them, 10 had AVE and 12 had moderate or severe aortic regurgitation, consistent with the previous findings.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This condition is often seen in patients with infective endocarditis of the aortic valve. Some reports have suggested that an infected aortic regurgitant jet is a likely cause of mitral valve aneurysms . Echocardiography shows the leaflet tissue of the mitral valve bulging into the left ventricle, forming a thin‐walled aneurysm‐like structure; (2) Fibrous diverticulum under the aortic valve, which may be caused by a congenital defect or weak development between the muscular ventricular wall and the annulus.…”
Section: Discussionmentioning
confidence: 99%